Pad and method for manufacturing same
By combining alumina fibers and refractory ceramic fibers in the pad and bonding with organic and inorganic binders, the problems of low surface pressure and easy shedding of existing pads are solved, and a high initial surface pressure and long-term maintenance effect are achieved.
Patent Information
- Application Number
- CN202510253897.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-10-04
- Filing Date
- 2025-03-05
- Publication Date
- 2025-06-03
- Estimated Expiration
- 2045-03-05
AI Technical Summary
The existing refractory ceramic fiber cushions have problems such as low surface pressure and easy discharge of exhaust gas treatment.
A cushion made of alumina fibers and refractory ceramic fibers is used. Alumina fibers account for 10% to 30% and refractory ceramic fibers account for 70% to 90% to 90% to Fiber. The fibers are bonded through organic binders and inorganic binders to form a pad material with high initial surface pressure and able to maintain surface pressure.
The initial surface pressure is achieved and the surface pressure can be maintained after repeated compression, preventing the waste gas treatment body from falling off, and improving the service life and effect of the pad material.
Smart Images

Figure CN120083588A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a forming mat and a method for manufacturing the same. Background Art
[0002] Exhaust gas discharged from an internal combustion engine such as a diesel engine contains particulate matter (hereinafter also referred to as PM). In recent years, the PM has become a problem for causing harm to the environment and the human body. In addition, since the exhaust gas also contains harmful gas components such as CO, HC, and NOx, there is also concern about the impact of such harmful gas components on the environment and the human body.
[0003] Therefore, as an exhaust gas purification device for collecting PM in exhaust gas or purifying harmful gas components, various exhaust gas purification devices have been proposed, which include: an exhaust gas treatment body made of a porous ceramic such as silicon carbide or cordierite, a housing that houses the exhaust gas treatment body, and a holding sealing material (mat material) disposed between the exhaust gas treatment body and the housing. The holding sealing material (mat material) is mainly disposed for the following purposes: preventing the exhaust gas treatment body from being damaged by contact with the housing covering its outer periphery due to vibrations or impacts generated during vehicle driving or the like; preventing exhaust gas from leaking from between the exhaust gas treatment body and the housing; and the like.
[0004] As such a mat material, Patent Document 1 discloses a mat that is a non-expansive mat containing heat-resistant amorphous inorganic fibers and is used for preparing a support for a brittle structure in a low-temperature exhaust gas treatment device, and contains alumina / silica fibers having about 50% of Al 2 O 3 and about 50% of SiO 2 .
[0005] Prior Art Documents
[0006] Patent Documents
[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 2002-531720 Summary of the Invention
[0008] Problems to be Solved by the Invention
[0009] The alumina / silica fibers having about 50% of Al 2 O 3 and about 50% of SiO 2 described in Patent Document 1 are fibers called refractory ceramic fibers. A mat made of such refractory ceramic fibers has a problem of low surface pressure, and the exhaust gas treatment body is likely to fall off due to the pressure of the exhaust gas.
[0010] The present invention is an invention completed in order to solve the above problems, and an object of the present invention is to provide a forming mat having a high initial surface pressure and capable of maintaining the surface pressure even when repeatedly compressed.
[0011] Means for Solving the Problem
[0012] That is, the forming mat of the present invention is a forming mat composed of two or more different inorganic fibers, an organic substance, and an inorganic substance, and is characterized in that the inorganic fibers include alumina fiber (AF) and refractory ceramic fiber (RCF), and the inorganic fibers are composed in a weight ratio of 10 wt% to 30 wt% of the alumina fiber and 70 wt% to 90 wt% of the refractory ceramic fiber.
[0013] The alumina fiber is hard. If the mat material is composed of alumina fiber, the initial surface pressure of the mat material becomes high. On the other hand, the refractory ceramic fiber is easily bent. If the mat material composed of the refractory ceramic fiber is repeatedly compressed, the refractory ceramic fiber is bent and the surface pressure decreases.
[0014] On the other hand, the refractory ceramic fiber is soft. If the mat material is composed of the refractory ceramic fiber, the initial surface pressure of the mat material decreases.
[0015] The forming mat of the present invention contains alumina fiber and refractory ceramic fiber, and thus achieves a balance between the effect of increasing the initial surface pressure of the mat material brought by the alumina fiber and the effect of maintaining the surface pressure when the mat material is repeatedly compressed brought by the refractory ceramic fiber.
[0016] Therefore, the forming mat of the present invention has a high initial surface pressure and can maintain the surface pressure even when repeatedly compressed.
[0017] In the forming mat of the present invention, the inorganic fibers are composed in a weight ratio of 10 wt% to 30 wt% of the alumina fiber and 70 wt% to 90 wt% of the refractory ceramic fiber.
[0018] If the weight ratio of the alumina fiber and the refractory ceramic fiber is within the above range, a balance between the two is achieved, and the effects of having a high initial surface pressure and being able to maintain the surface pressure even when repeatedly compressed can be appropriately exerted.
[0019] In the forming mat of the present invention, preferably, when randomly extracting any of the above inorganic fibers to determine whether it is alumina fiber or refractory ceramic fiber, the number of the alumina fibers is 3% or more, and the number of the refractory ceramic fibers is less than 97%.
[0020] If the ratio of the number of the alumina fiber and the refractory ceramic fiber is within the above range, a balance between the two is achieved, and the effects of having a high initial surface pressure and being able to maintain the surface pressure even when repeatedly compressed can be appropriately exerted.
[0021] In the forming mat of the present invention, preferably, the organic substance is an organic binder, and the inorganic substance is an inorganic binder.
[0022] The organic binder and the inorganic binder bond the inorganic fibers to each other to maintain the shape of the forming mat.
[0023] In addition, it is possible to suppress the inorganic fibers from falling off and scattering from the forming mat.
[0024] In the forming mat of the present invention, the glass transition temperature Tg of the above-mentioned organic binder is preferably 5°C or lower.
[0025] If the glass transition temperature Tg of the above-mentioned organic binder is 5°C or lower, the strength of the organic binder coating film formed by the organic binder can be improved, and a forming mat with a high elongation rate of the coating film and excellent flexibility can be produced.
[0026] In the forming mat of the present invention, the above-mentioned organic binder is preferably at least one selected from the group consisting of an acrylic resin that functions as a water-soluble organic polymer, an acrylate-based latex, a rubber-based latex, carboxymethyl cellulose, and polyvinyl alcohol, a styrene resin that functions as a thermoplastic resin, and an epoxy resin that functions as a thermosetting resin.
[0027] In addition, in the forming mat of the present invention, the above-mentioned inorganic binder preferably contains at least one selected from the group consisting of alumina, silica, silicon carbide, zirconia, boron nitride, diamond, and pumice.
[0028] These organic binders and inorganic binders are suitable for bonding the inorganic fibers to each other to maintain the shape of the forming mat.
[0029] The forming mat of the present invention is preferably produced by the following steps: a fiber opening step of opening the inorganic fiber preform in water to produce a slurry containing the opened inorganic fibers; and a forming step of forming the above-mentioned slurry into a forming mat.
[0030] In the fiber opening step, a plurality of fiber bundles formed by the interweaving of inorganic fibers are formed.
[0031] Such fiber bundles function as a core material, so that the surface pressure of the forming mat can be increased.
[0032] In the forming mat of the present invention, the above-mentioned inorganic fiber preform preferably contains a first inorganic fiber preform from a needle punched mat and / or a second inorganic fiber preform from a forming mat.
[0033] Regardless of whether the inorganic fiber preform is from a needle punched mat or from a forming mat, fiber bundles can be formed in the fiber opening step.
[0034] It should be noted that the above-mentioned first inorganic fiber preform preferably contains the above-mentioned alumina fiber.
[0035] In addition, the above-mentioned second inorganic fiber preform preferably contains the above-mentioned refractory ceramic fiber.
[0036] The forming mat of the present invention is preferably a forming mat obtained by forming in the above-mentioned forming process by batch forming or continuous forming.
[0037] By performing batch forming or continuous forming, the forming mat of the present invention can be easily obtained.
[0038] The forming mat of the present invention preferably contains a fiber bundle formed by intertwining 10 or more of the above-mentioned inorganic fibers in a twisted manner, and at least one of the fiber bundles in the fiber bundle is in a crimped state, and the drawing length of the crimped fiber bundle measured by the following drawing length measurement method is 0.1 mm or more longer than the length of the crimped fiber bundle.
[0039] Method for measuring the drawing length:
[0040] Place the crimped fiber bundle on a flat surface;
[0041] View the crimped fiber bundle after standing from above, draw from one end of the crimped fiber bundle to the other end along the crimped fiber bundle, and take the distance of this drawing as the "drawing length of the crimped fiber bundle".
[0042] The crimped fiber bundle has elasticity, and the surface pressure of the forming mat containing such a fiber bundle becomes higher.
[0043] The forming mat of the present invention preferably further contains organic fibrils as the above-mentioned organic matter.
[0044] It should be noted that the above-mentioned organic fibrils are preferably in a form in which cellulose, acrylic acid, aromatic polyamide, and PVA are fibrillated to raise fine fibers at the fiber ends and surfaces.
[0045] The manufacturing method of the forming mat of the present invention is a manufacturing method of a forming mat composed of two or more different inorganic fibers, organic matter, and inorganic matter. The characteristics are that the above-mentioned inorganic fibers include alumina fiber (AF) and refractory ceramic fiber (RCF), and the manufacturing method of the forming mat includes a forming process: forming a slurry containing the above-mentioned alumina fiber (AF) and the above-mentioned refractory ceramic fiber (RCF) to form a forming mat, and the above-mentioned inorganic fibers are composed of the above-mentioned alumina fiber in a weight ratio of 10 wt% to 30 wt% and the above-mentioned refractory ceramic fiber in a weight ratio of 70 wt% to 90 wt%.
[0046] By the manufacturing method of the forming mat of the present invention, the above-mentioned forming mat of the present invention can be manufactured.
[0047] In the manufacturing method of the forming mat of the present invention, the above-mentioned inorganic fibers are composed of the above-mentioned alumina fiber in a weight ratio of 10 wt% to 30 wt% and the above-mentioned refractory ceramic fiber in a weight ratio of 70 wt% to 90 wt%.
[0048] When the weight ratio of the alumina fiber and the refractory ceramic fiber is within the above range, a balance between the two is achieved, and a forming mat with a high initial surface pressure and capable of maintaining the surface pressure even when subjected to repeated compression can be manufactured.
[0049] In the method for manufacturing the forming mat of the present invention, preferably, when randomly extracting any of the above inorganic fibers from the above slurry to determine whether it is an alumina fiber or a refractory ceramic fiber, the number of the above alumina fibers is 3% or more, and the number of the above refractory ceramic fibers is less than 97%.
[0050] When the ratio of the number of the alumina fiber and the refractory ceramic fiber is within the above range, a balance between the two is achieved, and a forming mat with a high initial surface pressure and capable of maintaining the surface pressure even when subjected to repeated compression can be manufactured.
[0051] The method for manufacturing the forming mat of the present invention preferably includes a fibrillating step: fibrillating an inorganic fiber compact containing the above alumina fiber and the above refractory ceramic fiber in water to produce a slurry.
[0052] By performing the fibrillating step, a plurality of fiber bundles formed by interweaving inorganic fibers are formed.
[0053] Such a fiber bundle functions as a core material, and thus the surface pressure of the manufactured forming mat can be increased.
[0054] In the method for manufacturing the forming mat of the present invention, the above inorganic fiber compact preferably includes a first inorganic fiber compact from a needle-punched mat and / or a second inorganic fiber compact from a forming mat.
[0055] Regardless of whether the inorganic fiber compact is from a needle-punched mat or from a forming mat, fiber bundles can be formed in the fibrillating step.
[0056] It should be noted that the above first inorganic fiber compact preferably contains the above alumina fiber.
[0057] In addition, the above second inorganic fiber compact preferably contains the above refractory ceramic fiber.
[0058] In the method for manufacturing the forming mat of the present invention, preferably, in the above forming step, the above slurry contains organic fibrils as the above organic matter.
[0059] In addition, in the method for manufacturing the forming mat of the present invention, preferably, in the above fibrillating step, the organic fibrils are fibrillated in water to produce the above slurry.
[0060] Advantages of the Invention
[0061] According to the present invention, a forming mat with a high initial surface pressure and capable of maintaining the surface pressure even when subjected to repeated compression can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] Figure 1 FIG. 1 is a perspective view schematically showing an example of the forming mat of the present invention.
[0063] Figure 2 FIG. 2 is an enlarged view schematically showing an example of the inorganic fibers of the forming mat when the forming mat of the present invention contains fiber bundles.
[0064] Figure 3 FIG. 3 is a schematic view showing an example of the fiber bundle in a crimped state.
[0065] Figure 4 FIG. 4 is a cross-sectional view schematically showing an example of the exhaust gas purification device of the present invention. DETAILED DESCRIPTION OF THE INVENTION
[0066] Hereinafter, the forming mat of the present invention will be specifically described. However, the present invention is not limited to the following configuration, and can be appropriately modified and applied within the scope without changing the gist of the present invention. It should be noted that a configuration obtained by combining two or more of the following preferred configurations of the present invention is also the present invention.
[0067] The forming mat of the present invention will be described with reference to the drawings.
[0068] Figure 1 FIG. 1 is a perspective view schematically showing an example of the forming mat of the present invention.
[0069] As Figure 1 shown, the forming mat 10 is a rectangular forming mat made of inorganic fibers when viewed from above.
[0070] The forming mat 10 has a rectangular shape when viewed from above, with a convex portion 11a provided at one end portion 11 and a concave portion 12a provided at the other end portion 12.
[0071] As will be described in detail later, the forming mat 10 is wound around an exhaust gas treatment body and disposed in the exhaust gas purification device.
[0072] The convex portion 11a and the concave portion 12a are shaped to fit exactly when the forming mat 10 is wound around the exhaust gas treatment body.
[0073] If such a convex portion 11a and a concave portion 12a are provided, the sealing performance is improved when the forming mat 10 is disposed in the exhaust gas purification device described later.
[0074] The forming mat 10 contains an organic binder as an organic substance and an inorganic binder as an inorganic substance.
[0075] The organic binder and the inorganic binder bond the inorganic fibers to each other and maintain the shape of the forming mat 10.
[0076] In addition, it is possible to suppress the peeling off and scattering of inorganic fibers from the forming mat 10.
[0077] In addition, the forming mat 10 may also contain organic fibrils composed of cellulose, acrylic acid, aramid, PVA, etc. as organic substances.
[0078] The organic fibrils fibrillate with fine fibers (fibrils) from the ends and the surface, and the fine fibers are wound around the inorganic fibers to improve the adhesion.
[0079] The organic fibrils preferably have a form in which fine fibers are raised at the ends and the surface of the fibers composed of the above-mentioned organic substances.
[0080] In the forming mat 10, the inorganic fibers include alumina fibers (AF) and refractory ceramic fibers (RCF).
[0081] In addition, the inorganic fibers may also include other inorganic fibers other than alumina fibers and refractory ceramic fibers. Examples of other inorganic fibers include silica fibers, glass wool, rock wool, etc.
[0082] In this specification, "alumina fiber" refers to a fiber in which the weight ratio of Al 2 O 3 exceeds 60% by weight.
[0083] In this specification, "refractory ceramic fiber" refers to a fiber in which the weight ratio of Al 2 O 3 is 60% by weight or less.
[0084] As the alumina fiber, it is preferable to include a fiber containing Al 2 O 3 and SiO 2 , and the weight ratio is preferably Al 2 O 3 : SiO 2 = 70:30 to 80:20.
[0085] As the refractory ceramic fiber, it is preferable to include a fiber containing Al 2 O 3 and SiO 2 , and the weight ratio is preferably Al 2 O 3 : SiO 2 = 40:60 to 60:40.
[0086] The alumina fiber is hard. If the mat material is composed of alumina fiber, the initial surface pressure of the mat material becomes high. On the other hand, the refractory ceramic fiber is easily bent. If the mat material composed of refractory ceramic fiber is repeatedly compressed, the refractory ceramic fiber bends and the surface pressure decreases.
[0087] On the other hand, refractory ceramic fibers are soft. If the gasket material is made of refractory ceramic fibers, the initial surface pressure of the gasket material decreases.
[0088] The wet-laid gasket 10 contains alumina fibers and refractory ceramic fibers, and thus achieves a balance between the effect of increasing the initial surface pressure of the gasket material brought by the alumina fibers and the effect of maintaining the surface pressure when the gasket material is repeatedly compressed brought by the refractory ceramic fibers.
[0089] Therefore, the wet-laid gasket 10 has a high initial surface pressure and can maintain the surface pressure even when repeatedly compressed.
[0090] In the wet-laid gasket 10, the above-mentioned inorganic fibers are preferably composed in a weight ratio of 5 wt% or more of alumina fibers and less than 95 wt% of refractory ceramic fibers, and more preferably in a weight ratio of 10 wt% - 30 wt% of alumina fibers and 70 wt% - 90 wt% of refractory ceramic fibers.
[0091] If the weight ratio of the alumina fibers and the refractory ceramic fibers is within the above range, a balance between the two is achieved, and the effects of having a high initial surface pressure and being able to maintain the surface pressure even when repeatedly compressed can be appropriately exerted.
[0092] It should be noted that when it is desired to improve the softness of the wet-laid gasket 10, it is preferable to make the weight ratio of the alumina fibers less than 30 wt%, and when it is desired to make the wet-laid gasket 10 harder, it is preferable to make the weight ratio of the alumina fibers 30 wt% or more.
[0093] In the wet-laid gasket 10, when randomly extracting any of the above-mentioned inorganic fibers to determine whether they are alumina fibers or refractory ceramic fibers, it is preferable that the number of the above-mentioned alumina fibers is 3% or more and the number of the above-mentioned refractory ceramic fibers is less than 97%, and more preferably the number of alumina fibers is 20% - 50% and the number of the above-mentioned refractory ceramic fibers is 50% - 80%.
[0094] If the ratio of the number of the alumina fibers and the refractory ceramic fibers is within the above range, a balance between the two is achieved, and the effects of having a high initial surface pressure and being able to maintain the surface pressure even when repeatedly compressed can be appropriately exerted.
[0095] In the wet-laid gasket 10, relative to 100 parts by weight of the inorganic fibers, it is preferable to contain 0.1 part by weight - 20 parts by weight of an organic binder, and more preferably to contain 0.5 part by weight - 10 parts by weight.
[0096] In addition, relative to 100 parts by weight of the inorganic fibers, it is preferable to contain 0.1 part by weight - 10 parts by weight of an inorganic binder, and more preferably to contain 0.5 part by weight - 3.0 parts by weight.
[0097] The organic binder and the inorganic binder bond the inorganic fibers to each other to maintain the shape of the forming mat.
[0098] If the contents of the organic binder and the inorganic binder are within the above ranges, the bonding between the inorganic fibers becomes appropriate, and the flexibility and shape retention of the forming mat can be balanced.
[0099] In the forming mat 10, the glass transition temperature Tg of the organic binder is preferably 5°C or lower, more preferably -35°C to 5°C.
[0100] If the glass transition temperature Tg of the organic binder is 5°C or lower, the strength of the organic binder coating film formed by the organic binder can be increased, and a forming mat with a high elongation rate of the coating film and excellent flexibility can be produced.
[0101] In addition, when the forming mat 10 is wound around the exhaust gas treatment body, etc., mat breakage is less likely to occur. Furthermore, since the organic binder coating film does not become too hard, when the inorganic fibers break, the effect of connecting the inorganic fibers to each other can be exerted, and the scattering of the inorganic fibers can be suppressed.
[0102] An organic binder with a glass transition temperature Tg of less than -50°C is expensive, and the manufacturing cost becomes high.
[0103] When the glass transition temperature Tg of the organic binder exceeds 5°C, the flexibility of the forming mat sometimes decreases, and the elongation at break decreases.
[0104] In the forming mat of the present invention, the above-mentioned organic binder can be a water-soluble organic polymer, a thermoplastic resin, or a thermosetting resin.
[0105] Examples of the water-soluble organic polymer include acrylic resins, acrylate latexes, rubber latexes, carboxymethyl cellulose, and polyvinyl alcohol. Examples of the thermoplastic resin include styrene resins. Examples of the thermosetting resin include epoxy resins.
[0106] In the forming mat 10, the inorganic binder preferably contains at least one selected from the group consisting of alumina, silica, silicon carbide, zirconia, boron nitride, diamond, and pumice.
[0107] These organic binders and inorganic binders are suitable for bonding the inorganic fibers to each other to maintain the shape of the forming mat.
[0108] The forming mat 10 may include a fiber bundle formed by intertwining 10 or more of the above-mentioned inorganic fibers in a twisted manner.
[0109] The forming mat including such a fiber bundle will be described with reference to the drawings.
[0110] Figure 2It is an enlarged view schematically showing an example of the inorganic fibers of the forming mat when the forming mat contains fiber bundles in the present invention.
[0111] As Figure 2 shown, the forming mat may include a fiber bundle 21 formed by intertwining 10 or more inorganic fibers 20 in a twisted manner, and inorganic fibers 22 that do not form the fiber bundle 21.
[0112] The fiber bundle 21 may be in a straight state ( Figure 2 the state indicated by the symbol "21a" in Figure 2 ), or may be in a crimped state (
[0113] the state indicated by the symbol "21b" in
[0114] ). In this specification, a fiber bundle refers to a part in the forming mat where inorganic fibers are concentrated and intertwined, and the density is higher than other parts. Figure 2 The average length of the fiber bundle 21 (
[0115] the average value of the length indicated by the symbol L in Figure 2 ) is preferably 5 mm to 15 mm, more preferably 7 mm to 13 mm, and further preferably 8 mm to 10 mm.
[0116] It should be noted that, as Figure 2 shown, in the case of the fiber bundle 21a in a straight state and the fiber bundle 21b in a crimped state, the maximum width ( Figure 2 in which the lengths indicated by the symbols Wa and Wb respectively) is the width of the fiber bundle 21.
[0117] The fiber bundle 21 is formed by intertwining 10 or more inorganic fibers 20 in a twisted manner and supports each other, so it is not easily deformed by pressing. Therefore, when pressing is applied to the forming mat, the fiber bundle 21 acts as a core material and can relieve the pressing on the inorganic fibers 22 that do not form the fiber bundle 21. Therefore, it is possible to prevent the inorganic fibers 22 that do not form the fiber bundle 21 from being bent by pressing. As a result, the surface pressure of the forming mat increases.
[0118] In particular, in the case of the fiber bundle 21b in a crimped state, this effect is appropriately exerted, and the surface pressure of the forming mat is further increased.
[0119] If the average length of the fiber bundle is less than 5 mm, the fiber bundle is too short, and it is difficult for the fiber bundle to act as a core material to relieve the pressing on the inorganic fibers that do not form the fiber bundle.
[0120] If the average length of the fiber bundle exceeds 15 mm, since the fiber bundle is too long, it is likely to bend when pressed on the side of the fiber bundle, and it is difficult to function as a core material.
[0121] If the average width of the fiber bundle is less than 0.2 mm, the strength of the fiber bundle decreases, the fiber bundle is likely to bend, and it is difficult to function as a core material.
[0122] If the average width of the fiber bundle exceeds 1.0 mm, the strength of the fiber bundle becomes too high, and the softness of the entire forming mat decreases.
[0123] Hereinafter, the fiber bundle 21b in the crimped state will be described in detail with reference to the drawings.
[0124] Figure 3 It is a schematic diagram of an example of the fiber bundle in the crimped state.
[0125] In Figure 3 the fiber bundle 21b in the crimped state shown, the drawing length L of the fiber bundle 21b in the crimped state measured by the following drawing length measurement method is preferably t longer than the length L of the fiber bundle 21b in the crimped state, more preferably 0.1 mm or more longer, and further preferably 0.2 mm to 0.6 mm longer.
[0126] (Drawing length measurement method)
[0127] Place the fiber bundle 21b in the crimped state on a flat surface.
[0128] Next, observe the fiber bundle 21b in the crimped state after standing from above, and draw along the fiber bundle 21b in the crimped state from one end P 1 of the fiber bundle 21b in the crimped state to the other end P 2 , and take the distance L t of this drawing as the "drawing length of the fiber bundle in the crimped state".
[0129] When the drawing length L t of the fiber bundle 21b in the crimped state is longer than the length L of the fiber bundle 21b in the crimped state, the elasticity of the fiber bundle 21b in the crimped state is higher, and the surface pressure of the forming mat 10 is increased.
[0130] The forming mat 10 preferably includes the following fiber bundle 21b in the crimped state: in the fiber bundle 21b in the crimped state shown in Figure 3 , when measuring the "drawing length of the fiber bundle in the crimped state", the fiber bundle 21b in the crimped state can be drawn across the line segment S connecting the end P 1 and the end P 2 more than 2 times.
[0131] The degree of crimp of the fiber bundle 21b in such a crimped state is appropriate, the elasticity of the fiber bundle 21b in the crimped state is increased, and the surface pressure of the forming mat 10 is increased.
[0132] In the forming mat 10, it is preferable that the drawing length L of the fiber bundle 21b in the crimped state t The ratio to the length L of the fiber bundle 21b in the crimped state is L t / L = 1.1 to 1.6.
[0133] In the forming mat 10, the value of the following formula (1) is preferably 0.1 or more, more preferably 0.2 to 0.6.
[0134] (L t -L) / Wb...(1)
[0135] It should be noted that "Wb" refers to the width of the fiber bundle 21b in the crimped state.
[0136] In the forming mat 10, when the fiber bundle 21b in the crimped state is placed statically on a plane, the area of the fiber bundle 21b in the crimped state observed from above is preferably 2.6 mm 2 ~8.3 mm 2 .
[0137] In the forming mat 10, the proportion of the number of fiber bundles 21b in the crimped state contained in the fiber bundle 21 is preferably 85% or less, more preferably 60% or less, further preferably 30% or less, and even more preferably 10% to 30%.
[0138] The fiber bundle 21 is formed by intertwining a plurality of inorganic fibers 20 and supports each other, so it is not easily deformed by pressing. Therefore, when pressing is applied to the forming mat 10, the fiber bundle 21 functions as a core material and can relieve the pressing on the inorganic fibers 22 that do not form the fiber bundle 21. Therefore, it is possible to prevent the inorganic fibers 22 that do not form the fiber bundle 21 from being bent by pressing. As a result, the surface pressure of the forming mat 10 increases.
[0139] Next, an example of the manufacturing method of the forming mat of the present invention will be described.
[0140] An example of the manufacturing method of the forming mat of the present invention described below includes (1) a fiber opening step and (2) a forming step. Each step will be described below.
[0141] (1) Fiber opening step
[0142] In this step, an inorganic fiber compact containing alumina fibers and refractory ceramic fibers is opened in water to produce a slurry.
[0143] Since the slurry contains alumina fibers and refractory ceramic fibers, in the matting material manufactured through subsequent processes, it is possible to achieve a balance between the effect of increasing the initial surface pressure of the matting material brought about by the alumina fibers and the effect of maintaining the surface pressure when the matting material is repeatedly compressed by the refractory ceramic fibers.
[0144] Therefore, the manufactured wet-laid mat has a high initial surface pressure and can maintain the surface pressure even when repeatedly compressed.
[0145] It should be noted that in the above slurry, the above inorganic fibers are preferably composed of alumina fibers at 5 wt% or more and refractory ceramic fibers less than 95 wt%, and more preferably composed of alumina fibers at 10 wt% - 30 wt% and refractory ceramic fibers at 70 wt% - 90 wt%.
[0146] If the weight ratio of the alumina fibers and the refractory ceramic fibers is within the above range, a balance between the two is achieved, and the effects of having a high initial surface pressure and being able to maintain the surface pressure even when repeatedly compressed can be appropriately exerted.
[0147] In addition, in the above slurry, when randomly extracting any of the above inorganic fibers to determine whether they are alumina fibers or refractory ceramic fibers, it is preferable that the number of the above alumina fibers is 3% or more and the number of the above refractory ceramic fibers is less than 97%, and more preferably the number of alumina fibers is 20% - 50% and the number of the above refractory ceramic fibers is 50% - 80%.
[0148] If the ratio of the number of the alumina fibers and the refractory ceramic fibers is within the above range, a balance between the two is achieved, and it is possible to manufacture a wet-laid mat with a high initial surface pressure and capable of maintaining the surface pressure even when repeatedly compressed.
[0149] In addition, when the inorganic fiber preform is fibrillated, the inorganic fibers are not completely fibrillated, and fiber bundles formed by intertwining multiple inorganic fibers are formed.
[0150] Such fiber bundles function as core materials, so it is possible to increase the surface pressure of the manufactured wet-laid mat.
[0151] In the method for manufacturing the wet-laid mat of the present invention, the inorganic fiber preform preferably includes a first inorganic fiber preform from a needle-punched mat and / or a second inorganic fiber preform from a wet-laid mat.
[0152] Regardless of whether the inorganic fiber preform is from a needle-punched mat or a wet-laid mat, fiber bundles 21 can be formed in the fibrillation process.
[0153] It should be noted that the above first inorganic fiber preform preferably includes the above alumina fibers.
[0154] In addition, the above second inorganic fiber preform preferably includes the above refractory ceramic fibers.
[0155] As an example of fibrillation, the following method can be cited, for example.
[0156] First, the first inorganic fiber molded body and / or the second inorganic fiber molded body are fired at 700°C to 1000°C for 1.0 hour to 8.0 hours. The preferred firing temperature is 800°C to 950°C.
[0157] Thereby, the organic binder contained in the inorganic fiber molded body can be thermally decomposed, and the inorganic fiber molded body can be easily fibrillated.
[0158] Next, the fired inorganic fiber molded body is allowed to stand until it reaches room temperature, and then, the inorganic fiber molded body is untied by hand.
[0159] Next, the inorganic fiber molded body is added to water in an amount of 50 to 400 times by weight, and stirred to fibrillate, thereby producing a slurry containing inorganic fibers. This weight ratio is preferably 100 to 200 times by weight.
[0160] In addition, the stirring conditions are preferably set appropriately. For example, when producing 10 L of slurry, it is preferable to use (product name: SMT-101, manufacturer: AS ONE) as a stirrer and stir under the conditions of a rotation speed of 500 to 1000 rpm and a stirring time of 200 to 900 seconds. The preferred rotation speed is 650 to 850 rpm, and the stirring time is 500 to 700 seconds. More preferably, the rotation speed is 700 to 800 rpm, and the stirring time is 500 to 650 seconds.
[0161] Next, an organic binder and an inorganic binder are added to the slurry.
[0162] The organic binder is preferably added in an amount of 0.1 part by weight to 20 parts by weight with respect to 100 parts by weight of the inorganic fiber in the produced wet-laid mat, and more preferably in an amount of 0.5 part by weight to 15.0 parts by weight.
[0163] The inorganic binder is preferably added in an amount of 0.1 part by weight to 10 parts by weight with respect to 100 parts by weight of the inorganic fiber in the produced wet-laid mat, and more preferably in an amount of 0.5 part by weight to 3.0 parts by weight.
[0164] The preferred types of the organic binder and the inorganic binder have been described, so the description is omitted here.
[0165] (2) Wet-laying process
[0166] Next, the slurry is poured into a former having a filter mesh formed on the bottom surface, and the solvent in the slurry is desolvated to obtain an inorganic fiber aggregate. Then, the inorganic fiber aggregate is dehydrated and dried.
[0167] It should be noted that in the papermaking process, the inorganic fiber aggregate may be dried by heating and pressurizing. During heating and pressurizing, the inorganic fiber aggregate may be heat-treated by blowing hot air through it to dry it, or it may be kept wet without heat treatment.
[0168] In the case of heat treatment, in order to prevent the organic binder from deteriorating due to heat, the heating temperature and the hot air temperature are preferably 100°C to 250°C. Within the range of 100°C to 250°C, the degradation of the organic binder can be suppressed, and moisture can be dispersed from the inorganic fiber aggregate. When the heating temperature and the hot air temperature are less than 100°C, the temperature is not transmitted to the central part of the inorganic fiber aggregate, and the drying time becomes longer. In addition, if it exceeds 250°C, the organic binder is deteriorated, the restraining force between the fibers is reduced, and the thickness of the inorganic fiber aggregate becomes difficult to control.
[0169] Through the above steps, the papermaking mat of the present invention can be produced.
[0170] In addition, in the method for producing a paper-made mat of the present invention, it is preferable to carry out batch paper-making or continuous paper-making in the paper-making step.
[0171] The paper-made mat of the present invention can be easily obtained by batch paper-making or continuous paper-making.
[0172] In the above-mentioned method for manufacturing a paper-made mat, the paper-making process is carried out after the fiber-opening process, but in the method for manufacturing a paper-made mat of the present invention, the fiber-opening process may not be carried out as long as a slurry containing alumina fibers and refractory ceramic fibers can be prepared and paper-made to manufacture the mat material.
[0173] Next, a method of using the papermaking mat of the present invention will be described.
[0174] Figure 4 This is a cross-sectional view schematically showing an example of the exhaust gas purification device of the present invention.
[0175] like Figure 4 As shown, the exhaust gas purification device 100 includes a metal casing 30, an exhaust gas treatment body 40 accommodated in the metal casing 30, and a papermaking mat 10 disposed between the exhaust gas treatment body 40 and the metal casing 30. The papermaking mat 10 is the papermaking mat of the present invention.
[0176] The exhaust gas treatment body 40 is a columnar body with a plurality of cells 41 arranged in parallel along the length direction separated by cell walls 42. It should be noted that, at the end of the metal shell 30, an inlet pipe for introducing exhaust gas discharged from the internal combustion engine and an exhaust pipe for discharging the exhaust gas after passing through the exhaust gas purification device to the outside are connected as needed.
[0177] exist Figure 4In the exhaust gas purification device 100 shown, as the exhaust gas treatment body 40, an exhaust gas filter (honeycomb filter) in which any one of the respective channels is sealed with a sealing material 43 is used, but a catalyst carrier that is not sealed with a sealing material at either end face may also be used.
[0178] As Figure 4 shown, the exhaust gas ( Figure 4 in which G represents the exhaust gas and the arrow represents the flow of the exhaust gas) discharged from the internal combustion engine and flowing into the exhaust gas purification device 100 flows into one channel 41 that opens at the exhaust gas inflow side end face 40a of the exhaust gas treatment body (honeycomb filter) 40 and passes through the channel wall 42 that separates the channels 41. At this time, the PM in the exhaust gas is trapped by the channel wall 42, and the exhaust gas is purified. The purified exhaust gas flows out from other channels 41 that open at the exhaust gas outflow side end face 40b and is discharged to the outside.
[0179] As described above, the initial surface pressure of the forming mat 10 is high, and the surface pressure can be maintained even when subjected to repeated compression.
[0180] Therefore, in the initial stage of use of the exhaust gas purification device 100, even if the exhaust gas treatment body 40 is subjected to a high pressure from the exhaust gas, it is possible to prevent the exhaust gas treatment body 40 from falling off from the metal casing 30. In addition, the effect of preventing such falling off can be maintained for a long time.
[0181] The exhaust gas treatment body 40 may be made of a non-oxide porous ceramic such as silicon carbide or silicon nitride, or may be made of an oxide porous ceramic such as sialon, alumina, cordierite, or mullite. Among them, silicon carbide is preferred.
[0182] When the exhaust gas treatment body 40 is a porous ceramic made of silicon carbide, the porosity of the porous ceramic is not particularly limited, and is preferably 35% to 60%.
[0183] If the porosity is less than 35%, the exhaust gas treatment body may be clogged immediately. On the other hand, if the porosity exceeds 60%, the strength of the exhaust gas treatment body may be reduced and it may be easily damaged.
[0184] In addition, the average pore diameter of the porous ceramic is preferably 5 μm to 30 μm.
[0185] If the average pore diameter is less than 5 μm, PM may be easily clogged.
[0186] If the average pore diameter exceeds 30 μm, PM may pass through the pores and the PM cannot be trapped, and it cannot function as a filter.
[0187] It should be noted that the above porosity and pore diameter can be measured by a known method such as using a scanning electron microscope (SEM).
[0188] The pore density in the cross-section of the exhaust gas treatment body 40 is not particularly limited, and the preferred lower limit is 31.0 pores / cm 2 (200 pores / inch 2 ), and the preferred upper limit is 93.0 pores / cm 2 (600 pores / inch 2 ). Additionally, the more preferred lower limit is 38.8 pores / cm 2 (250 pores / inch 2 ), and the more preferred upper limit is 77.5 pores / cm 2 (500 pores / inch 2 ).
[0189] The exhaust gas treatment body 40 can also be loaded with a catalyst for purifying exhaust gas. As the loaded catalyst, noble metals such as platinum, palladium, and rhodium are preferred, and among them, platinum is more preferred. Additionally, as other catalysts, alkali metals such as potassium and sodium, and alkaline earth metals such as barium can also be used. These catalysts can be used alone or in combination of two or more.
[0190] If these catalysts are loaded, it is easy to burn and remove PM, and it can also purify toxic exhaust gas.
[0191] (Metal housing)
[0192] The metal housing 30 is approximately cylindrical.
[0193] The inner diameter of the metal housing 30 (the inner diameter of the part that houses the exhaust gas treatment body) is preferably slightly shorter than the diameter of the exhaust gas treatment body 40 around which the papermaking mat 10 is wound.
[0194] The metal housing 30 is not particularly limited, and it is preferably made of stainless steel.
[0195] The following matters are disclosed in this specification.
[0196] This disclosure (1) is a papermaking mat composed of two or more different inorganic fibers, organic substances, and inorganic substances, and is characterized in that the inorganic fibers include alumina fiber (AF) and refractory ceramic fiber (RCF).
[0197] This disclosure (2) is the papermaking mat as described in this disclosure (1), wherein the inorganic fibers are composed in a weight ratio of 5 wt% or more of the alumina fiber and less than 95 wt% of the refractory ceramic fiber.
[0198] This disclosure (3) is the papermaking mat as described in this disclosure (1) or (2), wherein when randomly extracting any of the above inorganic fibers to determine whether it is alumina fiber or refractory ceramic fiber,
[0199] The number of the above-mentioned alumina fibers is 3% or more, and the number of the above-mentioned refractory ceramic fibers is less than 97%.
[0200] The present disclosure (4) The forming mat according to any one of the present disclosures (1) to (3), wherein the above-mentioned organic substance is an organic binder, and the above-mentioned inorganic substance is an inorganic binder.
[0201] The present disclosure (5) The forming mat according to the present disclosure (4), wherein the glass transition temperature Tg of the above-mentioned organic binder is 5°C or lower.
[0202] The present disclosure (6) The forming mat according to the present disclosure (4) or (5), wherein the above-mentioned organic binder is at least one selected from the group consisting of acrylic resins, acrylate latexes, rubber latexes, carboxymethyl cellulose, and polyvinyl alcohol that function as water-soluble organic polymers, styrene resins that function as thermoplastic resins, and epoxy resins that function as thermosetting resins.
[0203] The present disclosure (7) The forming mat according to any one of the present disclosures (4) to (6), wherein the above-mentioned inorganic binder contains at least one selected from the group consisting of alumina, silica, silicon carbide, zirconia, boron nitride, diamond, and pumice.
[0204] The present disclosure (8) The forming mat according to any one of the present disclosures (1) to (7) is produced by the following steps: a fiber opening step of opening inorganic fiber formed bodies in water to produce a slurry containing the opened inorganic fibers; and a forming step of forming the above-mentioned slurry into a forming mat.
[0205] The present disclosure (9) The forming mat according to the present disclosure (8), wherein the above-mentioned inorganic fiber formed bodies include a first inorganic fiber formed body from a needle punched mat and / or a second inorganic fiber formed body from a forming mat.
[0206] The present disclosure (10) The forming mat according to the present disclosure (9), wherein the above-mentioned first inorganic fiber formed body contains the above-mentioned alumina fibers.
[0207] The present disclosure (11) The forming mat according to the present disclosure (9), wherein the above-mentioned second inorganic fiber formed body contains the above-mentioned refractory ceramic fibers.
[0208] The present disclosure (12) The forming mat according to any one of the present disclosures (8) to (11), wherein in the above-mentioned forming step, forming is performed by batch forming or continuous forming.
[0209] The present disclosure (13) A forming mat as described in any one of the present disclosures (1) to (12), wherein the forming mat includes a fiber bundle formed by intertwining 10 or more of the above-mentioned inorganic fibers in a twisted manner, at least one of the fiber bundles being in a crimped state, and the traced length of the fiber bundle in the crimped state measured by the following traced length measurement method is 0.1 mm or more longer than the length of the fiber bundle in the crimped state.
[0210] Method for measuring the traced length:
[0211] Place the fiber bundle in the crimped state on a flat surface;
[0212] View the fiber bundle in the crimped state after standing from above, and trace from one end of the fiber bundle in the crimped state to the other end along the fiber bundle in the crimped state, and take the traced distance as the "traced length of the fiber bundle in the crimped state".
[0213] The present disclosure (14) A forming mat as described in any one of the present disclosures (1) to (13), which further includes organic fibrils as the above-mentioned organic matter.
[0214] The present disclosure (15) A method for manufacturing a forming mat, which is a method for manufacturing a forming mat composed of two or more different inorganic fibers, organic matter, and inorganic matter, characterized in that the inorganic fibers include alumina fibers (AF) and refractory ceramic fibers (RCF), and the method for manufacturing the forming mat includes a forming process: forming a slurry containing the alumina fibers (AF) and the refractory ceramic fibers (RCF) to make a forming mat.
[0215] The present disclosure (16) A method for manufacturing a forming mat as described in the present disclosure (15), wherein the inorganic fibers are composed of the alumina fibers at 5 wt% or more and the refractory ceramic fibers less than 95 wt%.
[0216] The present disclosure (17) A method for manufacturing a forming mat as described in the present disclosure (15) or (16), wherein when randomly extracting any of the above-mentioned inorganic fibers from the slurry to determine whether they are alumina fibers or refractory ceramic fibers, the number of the alumina fibers is 3% or more, and the number of the refractory ceramic fibers is less than 97%.
[0217] The present disclosure (18) A method for manufacturing a forming mat as described in any one of the present disclosures (15) to (17), which further includes a fibrillating process: fibrillating an inorganic fiber compact containing the alumina fibers and the refractory ceramic fibers in water to make the above-mentioned slurry.
[0218] The manufacturing method of the wet-laid mat as described in the present disclosure (19), wherein the inorganic fiber formed body includes a first inorganic fiber formed body from a needle-punched mat and / or a second inorganic fiber formed body from a wet-laid mat.
[0219] The manufacturing method of the wet-laid mat as described in the present disclosure (20), wherein the first inorganic fiber formed body includes the alumina fiber.
[0220] The manufacturing method of the wet-laid mat as described in the present disclosure (21), wherein the second inorganic fiber formed body includes the refractory ceramic fiber.
[0221] The manufacturing method of the wet-laid mat as described in the present disclosure (22), wherein in the wet-laying process, the slurry further includes organic fibrils as the organic matter.
[0222] Examples
[0223] Hereinafter, examples that more specifically disclose the present invention are shown. It should be noted that the present invention is not limited to these examples.
[0224] (Example 1)
[0225] Prepare a first inorganic fiber formed body from a needle-punched mat, which is composed of alumina fibers with Al 2 O 3 :SiO 2 = 72:28 (weight ratio), with a bulk density of 0.17 g / mm 3 , and a stitch density of 21 stitches / cm 2 density.
[0226] Prepare a second inorganic fiber formed body from a wet-laid mat, which is composed of refractory ceramic fibers with Al 2 O 3 :SiO 2 = 50:50 (weight ratio), with a bulk density of 1.2 g / mm 3 .
[0227] Next, sinter the first inorganic fiber formed body and the second inorganic fiber formed body at 800 °C for 1 hour to thermally decompose the organic binder contained in the first inorganic fiber formed body and the second inorganic fiber formed body.
[0228] Next, leave the sintered first inorganic fiber formed body and the second inorganic fiber formed body to stand at room temperature, and then, manually untangle the first inorganic fiber formed body and the second inorganic fiber formed body.
[0229] Next, 7.0 g of the first inorganic fiber formed body and 3.0 g of the second inorganic fiber formed body were taken out and added to 0.4 L of water. After that, using a stirrer (product name: SMT-101, manufacturer: AS ONE), stirring was carried out at a rotation speed of 1000 rpm for 10 minutes to perform fiber opening, thereby producing a slurry of inorganic fibers.
[0230] It should be noted that 100 inorganic fibers were randomly extracted from the slurry to determine whether they were alumina fibers or refractory ceramic fibers. As a result, the proportion of alumina fibers was 71% and the proportion of refractory ceramic fibers was 29%.
[0231] In addition, with respect to 100 parts by weight of the inorganic fibers, the weight ratio of the alumina fibers was 70 parts by weight and the weight ratio of the refractory ceramic fibers was 30 parts by weight.
[0232] Next, an organic binder was added to the slurry in an amount of 0.5 parts by weight to 10 parts by weight with respect to 100 parts by weight of the inorganic fibers.
[0233] In addition, an inorganic binder was added to the slurry in an amount of 0.3 parts by weight to 3.0 parts by weight with respect to 100 parts by weight of the inorganic fibers.
[0234] Next, the slurry was poured into a former having a filter mesh formed on the bottom surface, and the solvent in the slurry was subjected to a desolvation treatment, thereby obtaining an inorganic fiber aggregate. After that, the inorganic fiber aggregate was dehydrated and dried under the conditions of 150°C to 210°C for 5 minutes to 1 hour, thereby manufacturing the wet laid mat of Example 1.
[0235] (Example 2), (Example 3) and (Comparative Example 1)
[0236] The first inorganic fiber formed body and the second inorganic fiber formed body used were adjusted. As shown in Table 1, the ratio (weight ratio) of the alumina fibers and the refractory ceramic fibers was changed. Except for this, the wet laid mats of Example 2, Example 3 and Comparative Example 1 were manufactured in the same manner as in Example 1.
[0237] [Table 1]
[0238]
[0239] (Measurement of surface pressure)
[0240] The wet laid mats of Example 1 to Example 3 and Comparative Example 1 were set on a testing machine (product name: SMT-101, manufacturer: AS ONE) and compressed at a speed of 25.4 mm / minute until the void bulk density (GBD) reached 0.40 mm 3 / g. With the void bulk density (GBD) reaching 0.40 mm 3The state of / g is maintained for 10 minutes. After that, the forming mat is released at a speed of 25.4 mm / minute.
[0241] This compression and release are carried out 1000 times. After that, the surface pressure of each forming mat is measured.
[0242] The results are shown in Table 1.
[0243] As shown in Table 1, it is shown that the forming mats of Examples 1 to 3 have a high surface pressure even when repeated compression and release are carried out repeatedly.
[0244] Symbol Explanation
[0245] 10 Forming mat
[0246] 11 One end
[0247] 11a Convex part
[0248] 12 The other end
[0249] 12a Concave part
[0250] 20, 22 Inorganic fiber
[0251] 21, 21a, 21b Fiber bundle
[0252] 30 Metal shell
[0253] 40 Exhaust gas treatment body
[0254] 40a Exhaust gas inflow side end
[0255] 40b Exhaust gas discharge side end
[0256] 41 Duct
[0257] 42 Duct wall
[0258] 43 Sealing material
[0259] 100 Exhaust gas purification device
Claims
1. A papermaking mat, which is composed of two or more different inorganic fibers, organic matter and inorganic matter, characterized in that: The inorganic fibers include alumina fibers AF and refractory ceramic fibers RCF, The inorganic fibers are composed of 10wt% to 30wt% of the alumina fibers and 70wt% to 90wt% of the refractory ceramic fibers.
2. The copying mat according to claim 1, wherein: When randomly extracting any of the inorganic fibers from the paper-made mat to determine whether it is alumina fiber or refractory ceramic fiber, The number of the alumina fibers is more than 3%, and the number of the refractory ceramic fibers is less than 97%.
3. The copying mat according to claim 1 or 2, wherein: The organic matter is an organic binder, and the inorganic matter is an inorganic binder.
4. The copying mat according to claim 3, wherein: The glass transition temperature Tg of the organic binder is 5° C. or less.
5. The copying mat according to claim 3, wherein: The organic binder is at least one selected from the group consisting of acrylic resin, acrylate latex, rubber latex, carboxymethyl cellulose and polyvinyl alcohol functioning as water-soluble organic polymers, styrene resin functioning as thermoplastic resins, and epoxy resin functioning as thermosetting resins.
6. The copying mat according to claim 3, wherein: The inorganic binder includes at least one of alumina, silicon dioxide, silicon carbide, zirconium oxide, boron nitride, diamond and pumice.
7. The copying mat according to claim 1 or 2, wherein: The paper-made mat comprises a fiber bundle formed by interweaving 10 or more inorganic fibers in a twisted manner, At least one of the fiber bundles is a crimped fiber bundle, The drawn length of the crimped fiber bundle measured by the following drawn length measuring method is longer than the length of the crimped fiber bundle by 0.1 mm or more, Method for measuring drawing length: The fiber bundle in a curled state is placed on a flat surface; Observe the curled fiber bundle after standing still from above, trace along the curled fiber bundle from one end to the other end of the curled fiber bundle, and define the traced distance as "the traced length of the curled fiber bundle".
8. The papermaking mat according to claim 1 or 2, further comprising organic fibrils as the organic matter.
9. A method for producing a paper-made mat comprising two or more different inorganic fibers, organic matter and inorganic matter, characterized in that: The inorganic fibers include alumina fibers AF and refractory ceramic fibers RCF, The method for manufacturing the paper-made mat comprises a paper-making step: paper-making a slurry containing the alumina fibers AF and the refractory ceramic fibers RCF to form a paper-made mat; The inorganic fibers are composed of 10wt% to 30wt% of the alumina fibers and 70wt% to 90wt% of the refractory ceramic fibers.
10. The method for producing a copy mat according to claim 9, wherein: When any of the inorganic fibers is randomly extracted from the slurry to determine whether it is an alumina fiber or a refractory ceramic fiber, The number of the alumina fibers is more than 3%, and the number of the refractory ceramic fibers is less than 97%.
11. The method for producing a papermaking mat according to claim 9 or 10, further comprising a fiber opening step of opening an inorganic fiber molded body comprising the alumina fibers and the refractory ceramic fibers in water to prepare the slurry.
12. The method for producing a copy mat according to claim 11, wherein: The inorganic fiber molded body includes a first inorganic fiber molded body derived from a needle punched mat and / or a second inorganic fiber molded body derived from a papermaking mat.
13. The method for producing a copy mat according to claim 12, wherein: The first inorganic fiber molded body includes the alumina fiber.
14. The method for producing a copy mat according to claim 12, wherein: The second inorganic fiber molded body includes the refractory ceramic fibers.
15. The method for producing a copy mat according to claim 9 or 10, wherein: In the papermaking step, the slurry further includes organic fibrils as the organic matter.
Citation Information
Patent Citations
Amorphous non-expanding inorganic fiber mat for low-temperature exhaust gas treatment equipment
JP2002531720A
Multilayer mounting mat for pollution control devices
CN102770630A
Inorganic fibers and molded body using same
CN104769169A
Pad, wound body, and method for manufacturing pad
CN117128072A
Pad and method for manufacturing same
CN118742689A